Germline PTEN Promoter Mutations and Deletions in Cowden/Bannayan-Riley-Ruvalcaba Syndrome Result in Aberrant PTEN Protein and Dysregulation of the Phosphoinositol-3-Kinase/Akt Pathway - Zhou, Xiao-Ping (The American Society of Human Genetics, 2003)
Germline intragenic mutations in PTEN are associated with 80% of patients with Cowden syndrome (CS) and 60% of patients with Bannayan-Riley-Ruvalcaba syndrome (BRRS). The underlying genetic causes remain to be determined in a considerable proportion of classic CS and BRRS without a polymerase chain reaction (PCR)-detectable PTEN mutation. We hypothesized that gross gene deletions and mutations in the PTEN promoter might alternatively account for a subset of apparently mutation-negative patients with CS and BRRS. Using real time and multiplex PCR techniques, we identified three germline hemizygous PTEN deletions in 122 apparently mutation-negative patients with classic CS (N=95) or BRRS (N=27). Fine mapping suggested that one deletion encompassed the whole gene and the other two included exon 1 and encompassed exons 1–5 of PTEN, respectively. Two patients with the deletion were diagnosed with BRRS, and one patient with the deletion was diagnosed with BRRS/CS overlap (features of both). Thus 3 (11%) of 27 patients with BRRS or BRRS/CS-overlap had PTEN deletions. Analysis of the PTEN promoter revealed nine cases (7.4%) harboring heterozygous germline mutations. All nine had classic CS, representing almost 10% of all subjects with CS. Eight had breast cancers and/or benign breast tumors but, otherwise, oligo-organ involvement. PTEN protein analysis, from one deletion-positive and five PTEN-promoter-mutation–positive samples, revealed a 50% reduction in protein and multiple bands of immunoreactive protein, respectively. In contrast, control samples showed only the expected band. Further, an elevated level of phosphorylated Akt was detected in the five promoter-mutation–positive samples, compared with controls, indicating an absence of or marked reduction in functional PTEN. These data suggest that patients with BRRS and CS without PCR-detected intragenic PTEN mutations be offered clinical deletion analysis and promoter-mutation analysis, respectively.